Elucidating the role of T cells in protection against and pathogenesis of dengue virus infections. (March 2014) - Mathew, Anuja; Townsley, Elizabeth; Ennis, Francis A
ABSTRACT: Dengue viruses (DENV) cause significantly more human disease than any other arbovirus, with hundreds of thousands of cases leading to severe disease in thousands annually. Antibodies and T cells induced by primary infection with DENV have the potential for both positive (protective) and negative (pathological) effects during subsequent DENV infections. In this review, we summarize studies that have examined T-cell responses in humans following natural infection and vaccination. We discuss studies that support a role for T cells in protection against and those that support a role for the involvement of T cells in the pathogenesis of severe disease. The mechanisms that lead to severe disease are complex, and T-cell responses are an important component that needs to be further evaluated for the development of safe and efficacious DENV vaccines.